In the shadow of the ancestors : the prehistoric foundations of the early Arabian civilization in Oman - Cleuziou, Serge, (Archaeopress Publishing Ltd, 2020)
Offering decades of archaeological research in the Oman Peninsula, the original 11 chapters are expanded and enhanced in this new edition by a number of new 'windows', written by a new generation of scholars, in order to include more recent research and interpretations.